Penerapan Model Pembelajaran Quantum Teaching dalam Meningkatkan Hasil Belajar Akidah Akhlak - N Siti Toyibah (Peneliti.net, 2021)
The low student learning outcomes are important to be researched by teachers. Classroom Action Research is a form of effort to improve student learning outcomes. This classroom action research aims to improve student learning outcomes in class IX D MTs N 2 Pangandaran in the Akidah Akhlak subject. This research uses Classroom Action Research (CAR) or Classroom Action Research, which is a research activity conducted in class on the teaching and learning process using the Quantum Teaching learning model which consists of 2 cycles. Each cycle consists of four stages, namely planning, acting, observing and evaluating the results of the action (observing) and reflecting until the expected improvement and improvement. The results showed that 27 out of 40 students or 67.5% had not reached the KKM. From the data analysis, it was found that students' completeness in cycle I reached 72.5% and cycle II reached 92.5% with an increase of 20%. with the number of students who completed as many as 37 students. Thus, the Quantum Teaching learning model can improve learning outcomes in the Akidah Akhlak subject for class IX D students at MTs Negeri 2 Pangandaran